Paradigma Kajian Keagamaan dalam Pluralitas Umat - Purwatma, Matheus (Jurnal Orientasi Baru, 2007)
Religions in a pluralistic society meet two main challenges, namely religious pluralism and the crying of the oppressed. Religious studies have to take serious consideration of the presense of other religions as well as to engage in an interreligious dialogue and to participate in the struggle of the oppressed. This article proposes religious studies that is both interreligious and liberative.